Pretty crowds are happy crowds: the influence of attractiveness on mood perception : psychological research [dataset] - Mertens, Alica; Hepp, Johanna; Voß, Andreas; Hische, Amelie (Universität, 2020)
Empirical findings predominantly support a happiness superiority effect in visual search and emotion categorization paradigms and reveal that social cues, like sex and race, moderate this advantage. A more recent study showed that the facial attribute attractiveness also influences the accuracy and speed of emotion perception. In the current study, we investigated whether the influence of attractiveness on emotion perception translates into a more general evaluation of moods when more than one emotional target is presented. In two experiments, we used the mood-of-the-crowd (MoC) task to investigate whether attractive crowds are perceived more positively compared to less attractive crowds. The task was to decide whether an array of faces included more angry or more happy faces. Furthermore, we recorded gaze movements to test the assumption that fixations on happy expressions occur more often in attractive crowds. Thirty-four participants took part in experiment 1 as well as in experiment 2. In both experiments, crowds presenting attractive faces were judged as being happy more frequently whereas the reverse pattern was found for unattractive crowds of faces. Moreover, participants were faster and more accurate when evaluating attractive crowds containing more happy faces as well as when judging unattractive crowds composed of more angry expressions. Additionally, in experiment 1, there were more fixations on happy compared to angry expressions in attractive crowds. Overall, the present findings support the assumption that attractiveness moderates emotion perception. (2020-02-07)